Prevalencia de brucella canis y Factores Asociados en Caninos Domésticos (canis familiaris) en el Barrio Mulaló Centro. - Cunalata Guato, Carlos Santiago (2019)
This project aimed to research the prevalence of Brucella canis and factors associated with domestic canines (Canis Familiaris), in the “Mulaló Centro” Neighborhood through C. Brucella Ab test method. 75 domestic canines were used as a sample to do this research project, considering age, sex and provenance. The samples obtained were taken by means of venipuncture in the cephalic vein, with an approximate average of 1cc, since the kit needs this minimum quantity for the interpretation of 10ul (1 drop) results, of which of the 75 samples analyzed is evidenced 4 positive canines to Brucella canis and coming from the “Mulaló Centro” neighborhood, with a percentage of 5 years ; As regards sex, a percentage of 68% males and 32% females was obtained. Based on the results obtained, the prevalence of Brucella canis does not have a very significant prevalence that influences the morbidity of the canines of “Mulaló Centro” Neighborhood, Latacunga Cantón, Cotopaxi Province.